KEMAMPUAN REPRESENTASI MATEMATIS SISWA STREESMUTPRAKAN SCHOOL THAILAND DALAM MENYELESAIKAN SOAL PISA - Bayu Exsanty Aribowo; Sunardi Sunardi; Erfan Yudianto (saintifika, 2021)
The ability of mathematical representation is very important to solve mathematical problems, because every solution must use mathematical representation. This research was conducted at Thailand's Streesmutprakan School because according to the results of the 2015 PISA test, mathematical representation skills also affected the execution of the PISA test. The PISA test results in 2015 showed that the Mathematics ability of Thai students was ranked 54th out of 70 countries with an average score of 415. While the average score for Mathematics from all countries taking the PISA test was 490. The results showed that Thailand was still in in a position below the average. The method used in this research is descriptive qualitative, by giving PISA questions about shape and space content. The results of this study indicate that students with high abilities are superior in visual mathematical representation. This can be seen from the number of cube nets that can be drawn with different models. The indicator of mathematical expression is only one of six students who can meet the indicator and answer correctly. For indicators of the ability to represent in words or written texts, students with high abilities are also more prominent because they have a reason for each answer, whereas for students with medium and low abilities only guess even silence during interviews.